WHAT EXPLAINS STUDENTS’ INTENTIONS TO PURSUE PUBLIC ACCOUNTANTS AS A CAREER? - Sidig, Danar Sutopo; Sinaga, Andar Ramona (Jurnal Akuntansi dan Keuangan Indonesia, 2020)
Public accountants play crucial roles in creating trustworthy information for economic development. Ironically, many parts of the world, including Indonesia, experience a shortage of Public Accountants despite the abundant number of accounting students. This study, built on the Theory of Planned Behaviour, aims to examine factors that explain students’ intentions to pursue public accountants as a career. To answer the question, this study uses questionnaires distributed to 115 accounting students from across Indonesia participating in CPA Days 2019. Utilising Structural Equation Modelling (SEM) technique to analyse their responses, this study has shown that students’ intentions are significantly affected by their attitude towards job-related factors. These factors involve their interests in the professions, time flexibility, learning opportunity, and dynamic environment provided by the jobs. On the contrary, their attitude toward public accountants’ social prestige, earnings potential, influence of others (subjective norm), as well as difficulties factors (perceived behavioural control) are not proven to be significant factors. This finding is not shocking, since it suits Generation Z behaviour in selecting their job. Therefore, to increase students’ interest to become public accountants, the professional body and regulator should promote the attributes of the professions matching to the Generation Z career aspirations.